The role of forensic accounting in winning compensation claims and its impact on the profits of the National Insurance Company: applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to shed light on the importance of forensic accounting and its role in winning compensation claims against the company because of the ability of the forensic accountant (the judicial expert) to interpret and analyze the data. The research community represents the insurance companies in Iraq. The research sample was represented by the National Insurance Company. Coverage of the theoretical and deductive approach in covering the practical side, based on the financial records of the National Insurance Company for years of research.One of the most important conclusions reached by the researchers was that forensic accounting has a role in the speedy settlement of financial cases, especially in lawsuits filed against the insurance company by winning the lawsuit and not paying compensation or reducing it.